2020
DOI: 10.1002/eat.23373
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between eating disorder duration and treatment outcome: Systematic review and meta‐analysis

Abstract: Objective: This systematic review and meta-analysis examine the contribution of duration to treatment outcome for eating disorders. Method: Studies (n = 31) were identified that examined associations (r) between duration and 45 different outcomes. We were unable to extract r for seven studies (9 outcomes) and extracted r for 36 outcomes across 24 studies (2,349 participants). Indicators of treatment outcome were heterogeneous and thus a series of different meta-analyses, aimed at increasing homogeneity, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 55 publications
0
34
1
1
Order By: Relevance
“…It is a surrogate marker of medical risk approximating to the need to access more intensive forms of treatment but there is uncertainty about its role as a prognostic or stage marker. Duration also has not always been found to be associated with a negative prognosis (Fernández-Aranda et al, 2020;Radunz, Keegan, Osenk, & Wade, 2020). However, in SHARED (multicentre OPD trial in UK) depression in combination with duration was associated with a worse outcome whereas duration alone did not (Ambwani et al, 2020).…”
Section: Markers Of Anorexia Nervosamentioning
confidence: 99%
“…It is a surrogate marker of medical risk approximating to the need to access more intensive forms of treatment but there is uncertainty about its role as a prognostic or stage marker. Duration also has not always been found to be associated with a negative prognosis (Fernández-Aranda et al, 2020;Radunz, Keegan, Osenk, & Wade, 2020). However, in SHARED (multicentre OPD trial in UK) depression in combination with duration was associated with a worse outcome whereas duration alone did not (Ambwani et al, 2020).…”
Section: Markers Of Anorexia Nervosamentioning
confidence: 99%
“…Disorders, fifth edition (DSM-5) and International Classification of Diseases 11th revision (ICD-11) (Ambwani et al, 2020;Krug et al, 2021;Radunz, Keegan, Osenk, & Wade, 2020). Both aspects (severity and enduringness) are dimensional and are not necessarily intercorrelated (Krug et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both aspects (severity and enduringness) are dimensional and are not necessarily intercorrelated (Krug et al, 2021). Some studies have reported no relationship between duration of illness and treatment outcome in EDs in general (Radunz et al, 2020), or for specific therapeutic approaches, such as cognitive behaviour therapy (CBT; Raykos, Erceg-Hurn, McEvoy, Fursland, & Waller, 2018), whereas other studies have found that duration of illness is associated with a poor outcome (Austin et al, 2021;Wild et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review regarding the diagnosis prevalence of EDs established that worldwide, around 8.4% of women and 2.2% of men will be diagnosed with this condition at some point in their lifetime [ 6 ]. The main treatments for EDs, which are based on cognitive–behavioral therapy (CBT), have been demonstrated to be useful in reducing symptoms [ 7 , 8 ]; however, these current treatments have not always reported successful outcomes [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%